2020
DOI: 10.3390/ijerph17165903
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Experimental Study on the Effect of Different Color of Safety Signs on a Virtual Subway Fire Escape—An Exploratory Case Study of Zijing Mountain Subway Station

Abstract: Safety signs play a very important role in people’s evacuation during emergencies. In order to explore the appropriate color for subway safety signs, four safety signs of different color combinations are designed, and the virtual reality, eye-tracking technology, and physiological indicator measurement are used in a virtual subway fire escape experiment. A total of 96 participants with equal distribution in gender and four different color combination groups were recruited. Participants’ eye-tracking and physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…As to test Hypotheses 1–14, a path analysis was further conducted via structural equation model (SEM) to evaluate the association among various factors [ 88 ]. SEM in this study is a systematic approach to examine research hypotheses holistically [ 88 ]. Figure 2 and Table 6 show the results of path analysis and the examination of hypotheses 1–14.…”
Section: Results and Findingsmentioning
confidence: 99%
“…As to test Hypotheses 1–14, a path analysis was further conducted via structural equation model (SEM) to evaluate the association among various factors [ 88 ]. SEM in this study is a systematic approach to examine research hypotheses holistically [ 88 ]. Figure 2 and Table 6 show the results of path analysis and the examination of hypotheses 1–14.…”
Section: Results and Findingsmentioning
confidence: 99%
“…As for model fit, the goodness-of-fit was measured by the following index [91]: standardized root mean square residual (SRMR), goodness-of-fit index (GFI), root mean square error of approximation (RMSEA), normed fit index (NFI), incremental fit index (IFI), Tucker-Lewis index (TLI), and comparative fit index (CFI) were generally within the respective thresholds, as shown in Table 5. Note: GFI = goodness-of-fit index; SRMR = standardized root mean square residual; RMSEA = root mean square error of approximation; NFI = normed fit index; IFI = incremental fit index; TLI = Tucker-Lewis index; CFI = comparative fit index.…”
Section: Model Fitmentioning
confidence: 99%
“…A lot of effort has been devoted to the design and effectiveness of warning signs in the past decades (Chan and Ng, 2010;Ma et al, 2010Ma et al, , 2018Chan and Ng, 2012;Bian et al, 2020;Zhu et al, 2020). In this research trend, the color of warning signs has also received considerable attention because color is essential when the textual message is restricted (Chapanis, 1994;Braun et al, 1995;Borade et al, 2008;Siu et al, 2017;Chen et al, 2020). White, yellow, orange, and red colors are found to be associated with successively greater perceived hazard levels (Chapanis, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Indian population, Borade et al (2008) demonstrated that certain colors signaled different hazard levels and suggested that population factors be considered in hazard communication. Moreover, it is indicated that a fire safety evacuation sign with "green and black" color leads to the lowest cognitive load, highest search efficiency, and best evacuation escape performance (Chen et al, 2020). Drawing from extant literature on sign colors, it could be seen that the findings are mixed and more research is needed to figure out which color is most effective for warning signs to communicate hazard information.…”
Section: Introductionmentioning
confidence: 99%